164 Examining the relationship between identity and injury fear avoidance: the influence of masculine and athletic identities. (3rd March 2020) - Cranswick, Ieuan; Jones, Ashley; Clarke, Phil; David, Tod
Abstract : Background: Sport, and specifically football, can foster increased masculine and athletic identities, which could potentially influence athletes' injury and rehabilitation-related related attitudes. Objective: To examine the relationships between masculinity, athletic identity, and athlete fear avoidance attitudes. Design: An observational, cross-sectional, study design was used. Correlational analyses examined the relationships between identity and fear avoidance variables. Setting: Male English professional football. Patients (or Participants): 72 academy players from northern professional football clubs within ∼1hour of the University completed a battery of identity and fear avoidance questionnaires. Interventions (or assessment of risk factors): All players completed a gender role conflict scale (GCRS), athletic identity measurement scale (AIMS), and an athlete fear avoidance questionnaire (AFAQ) during either a lab visit or as part of their training sessions. Main outcome measurements: Masculine role-related attitudes and conflicts were measured by the GRCS. Athletic identity was measured via the AIMS and the athlete's injury-related fear avoidance was record via the AFAQ. Results: Age was negatively correlated with total GRCS ( r =0.24, p=0.04), expressing emotion and affection with other men ( r = -.28, p=0.02), and work, life, & family interferences ( r = -.24, p=0.04). Athletic identity was associated with an increased fear of others' perceptions about an athlete's ability post-injury ( r = 0.31, p=0.007) and higher male affection concerns ( r = 0.28, p=0.03) and drives for male success, power, and competition ( r = 0.25, p=0.03). Conclusions: Younger footballers and those with higher athletic identities may be more susceptible to masculine role conflicts. Strongly identifying as an athlete and perceiving more work, life, and family conflicts can influence a fear of others' perceptions about the athlete's sporting abilities post-injury. Therapists may consider monitoring younger athletes' masculine and athletic identities. Identifying the potential gender-related conflicts or high levels of athletic identity could inform practitioners' approaches to rehabilitation to minimise a potential lack of disclosure or engagement regarding injury and rehabilitation respectively.